1978
DOI: 10.1017/s0022377800023229
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam excitation of ion-cyclotron waves and ion heating in plasmas with drifting electrons

Abstract: Ion-cyclotron waves are excited by a cesium ion beam in a cesium Q-machine plasma with drifting plasma electrons. These interactions differ significantly from those in the case of drifting ions in that the drifting electrons play an active role in the instability mechanism. The observed mode frequencies are slightly below those of the electron current driven modes. These waves can be convectively or absolutely unstable, depending on the ion beam velocity. For low beam velocities the instabifities are convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…The beam is given perpendicular energy by positioning the beam source off the cylindrical axis in an end region of converging magnetic field where the obliqueness of the beam to the magnetic field decreases with decreasing radial position. Hauck et al 62 investigate experimentally the excitation of ion-cyclotron waves by a purely axial ion beam by placing the beam source on the cylindrical axis.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…The beam is given perpendicular energy by positioning the beam source off the cylindrical axis in an end region of converging magnetic field where the obliqueness of the beam to the magnetic field decreases with decreasing radial position. Hauck et al 62 investigate experimentally the excitation of ion-cyclotron waves by a purely axial ion beam by placing the beam source on the cylindrical axis.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…Two factors may mitigate the preceding calculations; electron drift may reduce Landau damping, or the beams may be filamented. The effect of electron drift on ion beams has been noted by Hauck et al [1978], who showed that when the electron drift velocity is roughly equal and opposite to the ion beam velocity, the growth rate for the production of EHC waves by the ion beam is greatly enhanced. From the magnetometer data of Figure 9 we calculate a downward electron drift velocity of 1.25 x 102 km/s, while the ion beam velocity is upward at about 4 x 102 km/s.…”
Section: During This Period the •By Component Increases In The Positivementioning
confidence: 99%
“…At least two possible sources exist: electron drift in field-aligned currents and ion beams along the magnetic field, and evidence of both processes exist in the data. Furthermore, the two processes may interact by electron drift relaxation of the instability requirements for an ion beam [Hauck et al, 1978]. Of course, the two processes have quite different implications; the electron drift source converts the energy associated with field-aligned current to energetic ions, while the ion beam source produces strong pitch angle scattering in the ion beam.…”
Section: Production Of Ehc Wavesmentioning
confidence: 99%
“…Since ω/k z ν d > 1 for the higher-frequency eigenmode and ω/k z ν d < 0 for the lowerfrequency eigenmode, inverse Landau damping is not destabilizing the waves. The only other laboratory observation of spontaneously excited, electrostatic ion-cyclotron waves propagating antiparallel to the electron drift direction is the ion-beam-driven waves reported by Hauck et al (1978), but in this case the wave frequency normalized to the ion gyrofrequency does not upshift with experimental parameters. The amplitude of these non-resonant eigenmodes is not sensitive to the relative bias between the hot-plate the diskelectrode, as is the amplitude of the dissipative eigenmodes, implying that, as expected for predominantly reactive eigenmodes, they do not tap the free energy available in the parallel electron drift.…”
Section: Discussionmentioning
confidence: 82%